Development of Low Power LED Driver Using LTSpice Software - Muhammad Ikram, Mohd Rashid; Aim Izzuddin Hakimi, Mohamad Bekri (2013)
LED driver is regulated power supply designed to match the characeristics of an LED or array of LEDs in our application.